Strategic flexibility analysis in emergency medical service systems using decision rules - Zhou, Yuan; Cardin, Michel-Alexandre; Zhang, Sizhe (2018 IEEE 15th International Conference on Networking, Sensing and Control (ICNSC), 2018)
The capacity deployment of emergency medical service systems has been studied over decades. The design problem is still challenging due to the long-term uncertainty like the change of demographics. A novel approach in the form of multi-stage stochastic programming that considers flexibility in engineering design could be a valuable alternative to EMS infrastructure systems design. This paper proposes a hybrid algorithm to the stochastic model to improve its computational efficiency. The new algorithm outperforms other alternative methods in the numerical analysis by 3-6% in terms of quality of the solution, and is at least four times faster than the default methods.